History and historiography in constituting a region: The case of Kerala - Kesavan Veluthat
The formation of regions is as complex a process as the formation of countries or nations. Geography has much to do with it in some cases, languages in others. But political events, commercial networks and tribal or caste dominance can also play their part. History, actual or imagined, may be invoked to create regional consciousness. This article examines how owing to complex factors Kerala came to be identified as a definite region by the sixteenth century, so identified not only by its mainstream tradition but also by people external to it.